Becoming breastfeeding friendly in Great Britain—Does implementation science work?. (19th July 2022) - Kendall, Sally; Merritt, Rowena; Eida, Tamsyn; Pérez‐Escamilla, Rafael
Abstract: The Becoming Breastfeeding Friendly (BBF) in Great Britain study was conducted during 2017–2019 comprising three country studies: BBF England, Wales and Scotland. It was part of an international project being coordinated during the same period by the Yale School of Public Health across five world regions to inform countries and guide policies to improve the environment for the promotion, protection and support of breastfeeding. This paper reports on the application of the BBF process that is based on an implementation science approach, across the countries that constitute Great Britain (England, Wales and Scotland). The process involves assessing 54 benchmarks across eight interlocking gears that drive a country's 'engine' towards a sustainable policy approach to supporting, promoting and protecting breastfeeding. It takes a consensus‐oriented approach to the evaluation of benchmarks and the development of recommendations. This paper provides a critical overview of how the process was conducted, the findings and recommendations that emerged and how these were managed. We draw on critical theory as a theoretical framework for explaining the different outcomes for each country and some considerations for future action. Abstract : The Becoming Breastfeeding Friendly (BBF) in Great Britain study comprised three country studies: BBF England, Wales and Scotland. It was part of an international project to inform countries and guide policies to improve the environment for the promotion, protection and support of breastfeeding. This paper provides a critical overview of how the process was conducted, the findings and recommendations that emerged and how these were managed. Key messages: Undertaking an international, comparable approach to develop evidence‐based policy recommendations for scaling up the breastfeeding environment can provide useful data on which to draw explanations and conclusions on national variation. The findings from the BBF process across England, Scotland and Wales suggest that improving breastfeeding in Great Britain is dependent on the degree of political will and having a coordinated national breastfeeding strategy in place or not, along with access to robust breastfeeding data. A critical theory lens helps to bring to light some differences in the research and policy process that can explain differences between countries in the United Kingdom.